2011
DOI: 10.1124/dmd.111.039354
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Fluorescent Probe 1-Anilinonaphthalene-8-Sulfonate to the Measurement of the Nonspecific Binding of Drugs to Human Liver Microsomes

Abstract: ABSTRACT:The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Cell uptake of chloroquine was 2.3 fold higher in P-MDCK cells than wild type MDCK cells (p value = 1.598E −05 , n = 6); whereas, there was no significant difference in cell uptake of salicylic acid between transfected and wild type cells (Figure 5). The cell uptake of chloroquine was significantly higher than salicylic acid in both wild type as well as transfected MDCK cells, which is due to higher lipophilicity of chloroquine 24 as compared to salicylic acid 25 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Cell uptake of chloroquine was 2.3 fold higher in P-MDCK cells than wild type MDCK cells (p value = 1.598E −05 , n = 6); whereas, there was no significant difference in cell uptake of salicylic acid between transfected and wild type cells (Figure 5). The cell uptake of chloroquine was significantly higher than salicylic acid in both wild type as well as transfected MDCK cells, which is due to higher lipophilicity of chloroquine 24 as compared to salicylic acid 25 .…”
Section: Resultsmentioning
confidence: 93%
“…Chloroquine, a positively charged. lipophilic drug molecule 24 has high affinity for melanin pigment and is commonly used as a positive control for melanin binding 37 . In contrast, salicylic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, log P is clearly not the sole determinant of extensive NSB of TKIs to HLM. We and others have shown previously that NSB is generally highest for lipophilic organic bases with molecular masses .200 Da (Austin et al, 2002;Hallifax and Houston, 2006;Sykes et al, 2006;McLure et al, 2011). However, other physicochemical properties also influence the degree of NSB.…”
Section: Resultsmentioning
confidence: 99%
“…More generally, the choice of log P algorithm used for the prediction of NSB and other parameters warrants further investigation. Available evidence demonstrates that NSB, particularly of lipophilic basic drugs, arises largely from the partitioning of drugs into phospholipid membranes (Margolis and Obach, 2003;Nussio et al, 2007;McLure et al, 2011;Nagar and Korzekwa, 2012). Neutron diffraction studies with the charged lipophilic base propranolol showed that that the lipophilic naphthalene moiety partitions into the lipid bilayer, whereas the charged amine group apparently associates with the phospholipid head group (Herbette et al, 1983).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation